Strategies for collaboration between parents and teachers. (Journal of Parents and Teachers, 2025)
The article outlines a series of strategies to ensure ideal collaboration between parents and teachers. Among these strategies are: cordial, academic, bureaucratic, economic, technological, emerging, and participatory.
Keywords: collaboration; stratigies; teachers; parents